The Offices of the Registrar: The Milieu in Public Universities in Ghana - Dorcas Darkoah Kyeremeh; Millicent Pimpong; Portia Benny-Coffie (Journal of Education and Learning Technology)
This study explored the administrative challenges of the Registrar’s Offices in Ghanaian public universities, focusing on staffing shortages, infrastructure deficits, procurement delays, and limited professional development. Using survey data from 200 administrative staff, the findings revealed that technological gaps and bureaucratic inefficiencies undermine service delivery. The study applied Institutional and Resource Dependency Theories to highlight how compliance pressures and resource constraints limit operational efficiency. Recommendations call for policy reforms, capacity-building, and ICT investment to strengthen administrative performance in higher education. This study extends the literature on university administration by offering contextual insights into the Ghanaian higher education system, an area underrepresented in global academic discourse. It highlights the nuanced challenges of administrative leadership in low-resource environments and proposes adaptable frameworks that other developing nations can emulate.